2009
DOI: 10.1155/2009/956524
|View full text |Cite
|
Sign up to set email alerts
|

Irregular Polyomino-Shaped Subarrays for Space-Based Active Arrays

Abstract: This paper presents new results showing the application of polyomino-based subarrays to limited field of view and wideband, wide-angle scanning. This technology can reduce the number of phase controls in arrays used for limited sector coverage or the number of time delay devices for wideband radar or communications, and so can reduce the cost of space-based active arrays. We concentrate on the wideband application. Results are presented by comparing the gain and peak sidelobe results of irregular polyomino sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…Other satellite systems sometimes scan a high-directivity beam over even smaller angles to do detailed mapping [30]. Besides, fast electrical scanning in a narrow sector can also be combined with wide-angle mechanical rotation of the whole array.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other satellite systems sometimes scan a high-directivity beam over even smaller angles to do detailed mapping [30]. Besides, fast electrical scanning in a narrow sector can also be combined with wide-angle mechanical rotation of the whole array.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognised that the LFOV and WBWS applications for subarray technology exhibit similar behaviour and suffer the same deficiencies [30]. In fact, the above-mentioned applications (LFOV, WBWS and MSB) place similar requirements on subarray technology and array architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-arraying techniques are commonly used in the synthesis of array antennas, especially for large arrays as they allow to group the elements into sub-arrays reducing the number of control points in the feeding network [1][2][3][4][5][6][7][8][9][10][11]. The reduction in the complexity of the antenna architecture allows a sensible decrease in costs and a simplification in array manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies [1], [2] have shown that using irregular subarrays can greatly reduce quantization lobes that would otherwise result from the use of contiguous rectangular subarrays. Moreover, array cost can be reduced by filling the array Manuscript with a single type of polyomino subarray that is rotated in increments of 90 and flipped, to occupy eight different states, and by choosing the subarray size to be a power of two so that the subarrays can be fed using lossless, orthogonal power dividers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, array cost can be reduced by filling the array Manuscript with a single type of polyomino subarray that is rotated in increments of 90 and flipped, to occupy eight different states, and by choosing the subarray size to be a power of two so that the subarrays can be fed using lossless, orthogonal power dividers. Thus, there is no added complexity [1] at the subarray level, and the only complexity added is that the subarray feed locations are no longer on a rectangular grid. This change is readily addressed in the layout of the array corporate feed.…”
Section: Introductionmentioning
confidence: 99%